2019
DOI: 10.3390/ijerph16203829
|View full text |Cite
|
Sign up to set email alerts
|

“Youth Are More Aware and Intelligent than Imagined”: The Mountain Air Youth Photovoice Project

Abstract: Appalachian Kentucky reports some of the highest rates of respiratory illness in the United States, including chronic obstructive pulmonary disease and asthma. While smoking rates are high in the region, unexplained variation remains, and community-engaged research approaches are warranted to identify contributing factors. The Mountain Air Project’s community advisory board recommended that investigators invite youth to provide their perspectives on possible contributing factors to respiratory illness, and we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 15 publications
1
13
0
1
Order By: Relevance
“…Among the youth citizen scientists, we documented high rates of returned test kits and valid results. Our results using a citizen science approach, similar to other youth-focused community-engaged projects, demonstrated that youth participation can improve outcomes (in this case, radon testing) [ 10 , 11 , 12 , 13 , 17 ]. This project was consistent with the healthy environment dimension of the United Nations’ Sustainable Development Goals (SDG) for 2030.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Among the youth citizen scientists, we documented high rates of returned test kits and valid results. Our results using a citizen science approach, similar to other youth-focused community-engaged projects, demonstrated that youth participation can improve outcomes (in this case, radon testing) [ 10 , 11 , 12 , 13 , 17 ]. This project was consistent with the healthy environment dimension of the United Nations’ Sustainable Development Goals (SDG) for 2030.…”
Section: Discussionsupporting
confidence: 60%
“…However, collaborating with youth citizen scientists presents opportunities and potential benefits for both the youth and the research institution [ 10 , 11 , 12 ]. Engaging youth in research promotes youth empowerment and enhances the relationship between communities and academic institutions [ 11 , 13 ]. The purpose of this exploratory project was to assess the feasibility of the citizen science approach by engaging youth in the school setting to raise awareness of home radon testing in rural KY and suburban OH.…”
Section: Introductionmentioning
confidence: 99%
“…Most recommendations for future research focused on the individual project’s research or program area but a few addressed design and implementation related issues. These recommendations included addressing participation and communication challenges by embedding the photovoice project within a class or student organization (Cardarelli et al, 2019), assessing the time commitments of the participants (Foster-Fishman et al, 2010), and building an atmosphere of trust (Irby et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In the Mountain Air Project, one participant expressed their desire for the findings to be shared with their community and another said: “I feel proud to have been a part of something so active. I hope it will result in change” (Cardarelli et al, 2019). The “Health in my Community” project participants shared that the project “affected my perspective of what is my community,” and they felt they were “helping and doing something good” (Madrigal et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These themes included: compromises community members make regarding respiratory health in order to secure a livelihood; tension between cultural legacies and respiratory health; and consequences of geographic forces. This PV project demonstrated the value of deep understanding and analysis of environmental health concerns from the perspective of youth participation using PhotoVoice [ 18 ].…”
Section: Methodsmentioning
confidence: 99%